MiRNA‐765 mediates multidrug resistance via targeting BATF2 in gastric cancer cells. Issue 6 (18th April 2020) - Lin, Wan; Miao, Yu; Meng, Xiangkun; Huang, Ying; Zhao, Wanli; Ruan, Jigang
Abstract : Elucidation of the mechanisms underlying multidrug resistance (MDR) is required to ensure the efficacy of chemotherapy against gastric cancer (GC). To investigate this issue, here we identified that microRNA‐765 (miRNA‐765) is up‐regulated both in MDR GC cell lines and in specimens from patients who are not responding to chemotherapy. In addition, down‐regulation of miRNA‐765 increased the sensitivity of GC cells to anticancer drugs, whereas its overexpression had the opposite effect. Moreover, miRNA‐765 suppressed drug‐induced apoptosis and positively regulated the expression of MDR‐related genes. Finally, we showed that the basic leucine zipper ATF‐like transcription factor 2, a tumor suppressor gene, is the functional target of miRNA‐765. In summary, these results suggest that miRNA‐765 may promote MDR via basic leucine zipper ATF‐like transcription factor 2 in GC cells. Abstract : microRNA‐765 (miRNA‐765) is upregulated in multidrug‐resistant (MDR) gastric cancer (GC) samples. miRNA‐765 binds to the 3′ UTR of basic leucine zipper ATF‐like transcription factor 2 mRNA and inhibits basic leucine zipper ATF‐like transcription factor 2 expression, thereby suppressing drug‐induced apoptosis and positively regulating the expression of MDR‐related genes, characterized as increased viability of the tumor cells and decreased sensitivity to chemotherapy.